Innovative approaches to asthma treatment: harnessing nanoparticle technology - Vanshika Goswami; Kushneet Kaur Sodhi; Chandra Kant Singh (Discover Nano)
Abstract In the domain of respiratory illnesses, asthma remains a critical obstacle. The heterogeneous nature of this chronic inflammatory disease poses challenges during its treatment. Glucocorticoid-based combination drug therapy now dominates clinical treatments for asthma; however, glucocorticoid resistance, numerous adverse effects, the incidence of inadequate drug delivery, and other factors need the development of more effective therapies. In recent years, there has been extensive research on nanotechnology in medicine. It has been shown in studies that these drug delivery systems can greatly enhance targeting and bioavailability and decrease the toxicity of medication. Nanoparticle drug delivery systems offer improved therapeutic efficacy compared to conventional administration techniques. Nanotechnology enables advancements in precision medicine, offering benefits for heterogeneous conditions such as asthma. This review will examine the critical factors of asthma to consider when formulating medications, as well as the role of nanomaterials and their mechanisms of action in pulmonary medicine for asthma treatment.